A novel alkali-activated cement from mineral admixture, superabsorbent polymers, and alkali-doped carboxylate glass. (20th June 2023) - Qu, Min; Wang, Fazhou; Liu, Peng; Macphee, Donald E.; Hu, Chuanlin; Yang, Lu
Highlights: A novel ternary alkali-activated cement. A new type of alkali activator which could control the release rate of alkali and delivery of alkali in situ . Alkali is encapsulated within the alkali-doped carboxylate glass. The water-saturated SAP works in cement as water supplier and internal curing agent. Abstract: In this paper, we introduce a novel approach for the targeted delivery of concentrated alkali required for activation of aluminosilicate-based cements, which avoids exposure to caustic solutions on site. The solid alkali, encapsulated within a water-soluble glass (alkali-doped carboxylate glass) is dry blended with mineral admixtures (ground granulated blast slag and fly ash) and water saturated superabsorbent polymers (SAP, being the only source of mix water in this study). The solubility of alkali-doped carboxylate glasses (ACG) was characterized. The hydration of ground granulated blast slag (GGBS) and fly ash (FA) with different curing times were monitored by SEM, XRD, FT-IR and solid-state MAS NMR, which showed the co-existence of calcium aluminum silicate hydrate (C-A-S-H) gel and sodium aluminosilicate hydrate (N-A-S-H) gel in the hydration products. The mechanical properties of AAC were tested, and the compressive strength of AAC (using ACG as alkali activator, water saturated SAP as water source) reached over 40 MPa after curing for 28 days.